Effects of different chicken manure rates of on early growth of fig (Ficus Carica) - Azmi, Fatin Munirah; Muhamad Tajudin, Nur Shuhada; Shahari, Rozilawati; Che Amri, Che Nurul Aini (Zibeline International Publisher, 2019)
Fertilizing by using chicken manure as an organic amendment is a complementary to improve chemical fertilizer efficiency. This study was conducted in Glasshouse & Nursery Complex of IIUM with the objectives of evaluating different rates of chicken manure application on soil properties, leaf nutrients and the growth response of fig trees for early growth effects. The soils were amended with 0%, 10%, 20%, 30% and 50% of chicken manure on three months old saplings of cultivar BTM6 in five replications were used to observe the effects. The experiment was observed for three months. The nutrient content in T1 and treated soil showed a significant difference at p < 0.05. The T5 had the highest content of nutrients compared to other treatments. However, the leaf nutrient contents did not show any significant difference among all treatments. Survivability of the trees were 100% with T2 showed a superlative growth response with the high number of branches, leaves and fruits